To find the numerical equivalent, we can simplify the expression using the rules of exponents.
First, we can apply the rule that states when multiplying two numbers with the same base, we add their exponents.
So, 2^5 ⋅ 2^(-2) = 2^(5 + (-2)) = 2^3.
Then, we simplify using the rule that says when raising a number to a positive exponent, we multiply the base by itself that many times.
In this case, 2^3 = 2 × 2 × 2 = 8.
Therefore, the numerical equivalent of 2^5 ⋅ 2^(-2) is 8.
Find the numerical equivalent of 2^5 ⋅2^−2
1 answer